Clause Structure in the Rai Dialect of the Kaili Language: A Descriptive Syntactic Study - Floryasita Wulinda; Fitra Ramadhani; Haerunnisa Haerunnisa; Ira Safitri (Civiliza Publishing, Indonesia., 2026)
Language is an important element in human life because it functions as a means of communication, conveying ideas, and a medium for inheriting cultural values from one generation to the next. This study aims to describe the structure, types, and rules of word formation through derivation, as well as the differences and syntactic relationships between independent clauses (free) and dependent clauses (bound) in the Kaili language of the Rai dialect, one of the varieties of Kaili language used in the Central Sulawesi region. The research uses a qualitative descriptive method; The data was collected through the Simak and Cakap method (interviews with native speakers, natural speech recordings), then analyzed using the matching and distribution method to identify the patterns, functions, and grammatical features. The results show that independent clauses can stand on their own as complete sentences, consisting of three main types: intransitive (without objects, S-P, P-S, and variations with adverbs), transitive (having objects, the basic pattern of S-P-O and its variations), and equivocal (connecting subjects and complements, without mandatory verbs). In contrast, dependent clauses cannot stand alone, function as part of compound sentences (as complements, adverbs, or adverbs), and are usually characterized by subordinate conjunctions or suffixes that mark syntactic dependencies on the main clause. At the morphological level, derivation is the process of forming new words with different meanings and classes of words, especially through suffixes (prefixes, suffixes, circumfixes) that are commonly used in this dialect. Suffixes such as na-, po-, ma-, pa- change the verb to a noun, change the active-passive meaning, or change the category of a word, for example from an adjective to a verb; This process becomes an important means of enriching vocabulary and composing more complex sentence structures. Overall, the syntactic and morphological system of the Rai dialect exhibits the characteristics of the Kaili language: a flexible but head-beginning pattern of word order, the productive use of suffixes for the derivation and marking of relationships between clauses, and a clear distinction between independent units and those that depend on sentence structure.